You're invited eaudiobook - Jayatissa, Amanda (Penguin Audio, 2022)
“Absolutely addictive…it’s like Agatha Christie meets Crazy Rich Asians . Amanda Jayatissa is an author you want to watch.”—Brad Thor What could be worse than your ex-boyfriend marrying your childhood best friend? Getting accused of her murder… From the award-winning author of My Sweet Girl comes a dangerously addictive thriller about a lavish Sri Lankan wedding celebration that not everyone will survive. When Amaya is invited to Kaavi’s over-the-top wedding in Sri Lanka, she is surprised and a little hurt to hear from her former best friend after so many years of radio silence. But when Amaya learns that the groom is her very own ex-boyfriend, she is consumed by a single thought: She must stop the wedding from happening, no matter the cost.  But as the week of wedding celebrations begin and rumors about Amaya’s past start to swirl, she can’t help but feel like she also has a target on her back. When Kaavi goes missing and is presumed dead, all evidence points to Amaya.  However, nothing is as it seems as Jayatissa expertly reveals that each wedding guest has their own dark secret and agenda, and Amaya may not be the only one with a plan to keep the bride from getting her happily ever after…